Data on multiple regression analysis between boron, nickel, arsenic, antimony, and biological substrates in horses: The role of hematological biomarkers. Issue 2 (10th November 2021) - Giannetto, Claudia; Fazio, Francesco; Nava, Vincenzo; Arfuso, Francesca; Piccione, Giuseppe; Coelho, Clarisse; Gugliandolo, Enrico; Licata, Patrizia
Abstract: The objective of this study was to evaluate the biomarkers of exposure to boron, nickel, arsenic, and antimony in an industrial region, evaluating the bioaccumulation in biological substrates and the correlation with biomarkers such as hematological parameters. Through indication of the accumulation of some minerals in the horse's biological substrates reflects environmental pollution. Moreover, an additional aim of the study was to show whether these contaminants have an influence on the hematological parameters in horses. Blood, serum, mane, and tail samples from 20 horses from an industrial area were analyzed to determine boron (B), nickel (Ni), arsenic (As), antimony (Sb) concentration. Hematological parameters (red blood cell [RBC], white blood cells [WBC], hemoglobin [Hb], hematocrit [Hct], mean corpuscular volume [MCV], mean corpuscular hemoglobin [MCH], mean corpuscular hemoglobin concentration [MCHC], platelet [PLT]) as a biomarker of blood in relation to the bioaccumulation of these elements were analyzed also. Descriptive statistical analysis was performed and single regression analysis (Pearson) and multiple regression analysis ( p  < 0.05) between blood factors, As, B, Ni, and Sb concentrations, and for each mineral in different substrate, respectively. Results showed a significant correlation between tail and mane concentrations with serum and blood for boron concentration ( r  = −1 p  < 0.05). No significant correlation between sample (feed, hay, mane, tail, and water) concentrations and As, Ni, and Sb were found. A significantly negative correlation with blood parameters ( r  = −1 p  < 0.05) was observed in Boron concentration for mane and tail. This suggests that the mane and tail may be a potential means to investigate suspected exposure to excessive levels of trace minerals.